2015
DOI: 10.3109/0886022x.2015.1073557
|View full text |Cite
|
Sign up to set email alerts
|

Role of P311 in interleukin-1α-induced epithelial to myofibroblast transition in kidney tubular epithelial cells

Abstract: Tubular epithelial-myofibroblast transition (TEMT) is an important process in renal tubulointerstitial fibrosis. Interleukin-1α (IL-1α) and transforming growth factor-β1 (TGF-β1) have been demonstrated to be key inducers of TEMT. In mouse embryonic fibroblast cells (NIH3T3), P311 protein induces phenotypic changes that are consistent to myofibroblast transformation. In the present study, we investigated the role of P311 gene and protein as well as potential mechanisms underlying TEMT in normal rat kidney tubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…However, little is known regarding the roles performed by and regulation of EpMyT during skin wound healing. Recent studies using rat kidney epithelial cell lines have shown that P311 may promote IL-1α-induced EMT via a TGFβ1-independent pathway [31] and that it may inhibit TGFβ1-induced EMT by blocking the Smad/ILK pathways [32]. Furthermore, our recent in-vivo study showed that P311 promotes renal fibrosis via the TGFβ1/Smad signaling [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known regarding the roles performed by and regulation of EpMyT during skin wound healing. Recent studies using rat kidney epithelial cell lines have shown that P311 may promote IL-1α-induced EMT via a TGFβ1-independent pathway [31] and that it may inhibit TGFβ1-induced EMT by blocking the Smad/ILK pathways [32]. Furthermore, our recent in-vivo study showed that P311 promotes renal fibrosis via the TGFβ1/Smad signaling [33].…”
Section: Discussionmentioning
confidence: 99%
“…Lei et al found that at concentrations of 10, 50 and 100 μmol/L, salidroside could reverse the hypertrophy and elongation of proximal renal tubular epithelial cells induced by cobalt chloride in hypoxic rats, showing the appearance of myoblasts. Salidroside inhibits the expression of TGF-β1 and HIF-1α, reduces the increase of extracellular matrix such as α-SMA, collagen I and fibronectin, and inhibits the transdifferentiation of hypoxic renal tubular epithelial cells-myofibroblasts (Zhang et al, 2010).…”
Section: Other Kidney Injurymentioning
confidence: 99%
“…IL-1 is capable of inducing morphological and phenotypic transdifferentiation of a normal rat tubular epithelial cell line into myofibroblast-like cells (Vesey et al 2002). IL-1β, as a much stronger inducer of nuclear factor (NF)-κB response, interacts with IL-1 receptor (IL-1R) to induce EMT by activating the IL-1/IL-1R/NF-κB signaling pathway (Dinarello and Wolff 1993;Gasse et al 2007;Zhang et al 2015). The NF-κB complex is usually inactive and located in the cytoplasm while bound to IκB inhibitor proteins; however, after activation of IL-1/IL-1R/NF-κB signaling, NF-κB is activated and translocates to the nucleus, where it forms the p65/p50 complex to control target gene transcription (Gupta et al 2010;Zheng et al 2011).…”
Section: Introductionmentioning
confidence: 99%